EDITORIAL - Acevedo Borrego, Adolfo (2014)
The Research Institute of the Faculty of Industrial Engineering is spread through much of their contributions as other universities nationally and internationally for Industrial Data magazine, which this time presents 16 research papers divided into three sections level: production and Management, Design and Technology, and Systems and Informatics; the quality and relevance of the articles published in this journal offers readers the opportunity to meet and investigate everything that has been offering the service of companies , educational institutions and society as a whole, to support resolve the multiple problems that afflict and titillation to develop other research.